Synergism between Thrombin and Epinephrine in Human Platelets: Different Dose-Response Relationships for Aggregation and Dense Granule Secretion - Steen, Vidar M; Holmsen, Holm (Thrombosis and Haemostasis, 1985)
Synergism between epinephrine and thrombin in human gel-filtered platelets was studied. Suspensions of platelets, which did not contain added fibrinogen, were incubated at 37° C to measure aggregation and dense granule secretion after stimulation. Both aggregation and secretion induced with 0.03-0.3 U/ml of thrombin were markedly potentiated by epinephrine (0.5-4 ҼM), which alone was without effect. Addition of epinephrine before stimulation with thrombin resulted in a marked decrease in the concentration of thrombin required for half-maximal aggregation, without affecting the maximal aggregation response. The dose-response relationship for dense granule secretion was affected in a similar way with regard to the half-maximal response; in addition, epinephrine slightly increased maximal secretion response. However, the concentration range for thrombin at which synergism occurred was distinctly lower for aggregation than for secretion. Our observations suggest that aggregation and dense granule secretion are separate steps in the sequence of stimulus-response coupling, and suggest distinct thresholds of intracellular messengers for these different responses.
Keywords: Human gel-filtered platelets; Thrombin; Epinephrine; Synergism; Secretion; Aggregation